Association between the risk and severity of Parkinson’s disease and plasma homocysteine, vitamin B12 and folate levels: a systematic review and meta-analysis - Quan, Yuxin; Xu, Jisen; Xu, Qing; Guo, Zhiqing; Ou, Ruwei; Shang, Huifang; Wei, Qianqian (Frontiers in Aging Neuroscience, 2023)
Background Parkinson’s disease (PD) is recognized as the second most prevalent progressive neurodegenerative disease among the elderly. However, the relationship between PD and plasma homocysteine (Hcy), vitamin B12, and folate has yielded inconsistent results in previous studies. Hence, in order to address this ambiguity, we conducted a meta-analysis to summarize the existing evidence. Methods Suitable studies published prior to May 2023 were identified by searching PubMed, EMBASE, Medline, Ovid, and Web of Science. The methodological quality of eligible studies was assessed using the Newcastle-Ottawa Quality Assessment Scale (NOS). Meta-analysis and publication bias were then performed using R version 4.3.1. Results The results of our meta-analysis, consisting of case–control and cross-sectional studies, showed that PD patients had lower folate and vitamin B12 levels (SMD [95%CI]: −0.30[−0.39, −0.22], p < 0.001 for Vitamin B12; SMD [95%CI]: −0.20 [−0.28, −0.13], p < 0.001 for folate), but a significant higher Hcy level (SMD [95%CI]: 0.86 [0.59, 1.14], p < 0.001) than healthy people. Meanwhile, PD was significantly related to hyperhomocysteinemia (SMD [95%]: 2.02 [1.26, 2.78], p < 0.001) rather than plasma Hcy below 15 μmol/L (SMD [95%]: −0.31 [−0.62, 0.00], p = 0.05). Subgroup analysis revealed associations between the Hcy level of PD patients and region (p = 0.03), age (p = 0.03), levodopa therapy (p = 0.03), Hoehn and Yahr stage (p < 0.001), and cognitive impairment (p < 0.001). However, gender (p = 0.38) and sample size (p = 0.49) were not associated. Conclusion Hcy, vitamin B12, and folic acid potentially predict the onset and development of PD. Additionally, multiple factors were linked to Hcy levels in PD patients. Further studies are needed to comprehend their roles in PD.